Pengembangan Strategi Pemanfaatan Media Sosial Dalam Penerimaan Mahasiswa Baru - Muhammad Faisal Rahman; Juliana Kurniawati; Fitri Nur Hafidzah (Jurnal Khabar: Komunikasi dan Penyiaran Islam, 2025)
This study aims to formulate development strategies to optimize social media use in supporting the student admission process at Universitas Muhammadiyah Bengkulu (UMB). Using a mixed-methods approach, quantitative data were gathered from 100 respondents via online questionnaires, while qualitative data were obtained from 16 purposively selected informants through interviews. The analysis employed SWOT, IFE (Internal Factor Evaluation), and EFE (External Factor Evaluation) frameworks. Results identified 12 strategies classified into SO, WO, ST, and WT categories. With an IFE score of 2.79 and an EFE score of 2.64, UMB falls into Quadrant V, indicating a "hold and maintain" position. The recommended strategies align with the 4P marketing mix: promotion through active and targeted social media campaigns, product represented by engaging and relevant digital content, place by utilizing accessible online platforms such as Instagram and TikTok, and price reflected in cost-efficiency by leveraging student involvement and influencers instead of high-budget marketing. These strategies aim to increase visibility, build a strong institutional image, and enhance UMB’s competitiveness in attracting prospective students.